Risk Factors for Cerebral Infarction After Moderate or Severe Traumatic Brain Injury - Wu Y (Dove Medical Press, 2021)
Yin-gang Wu,1,2 Yingjiu Chao,1 Ge Gao,1 Dejun Bao,1 Yongfei Dong,1 Xiangpin Wei,1 Chaoshi Niu1,2 1Department of Neurosurgery, The First Affiliated Hospital of USTC, Division of Life Sciences and Medicine, University of Science and Technology of China, Hefei, Anhui, 230001, People’s Republic of China; 2Brain Function and Brain Disease Anhui Provincial Key Laboratory, Hefei, Anhui, 230001, People’s Republic of ChinaCorrespondence: Chaoshi NiuDepartment of Neurosurgery, The First Affiliated Hospital of USTC, Division of Life Sciences and Medicine, University of Science and Technology of China, Hefei, Anhui, 230001, People’s Republic of ChinaTel +86 18963788788Email niuchaoshi@126.comPurpose: Posttraumatic cerebral infarction (PTCI) is a common and relatively serious complication of traumatic brain injury (TBI) without a clear etiology. Evaluating risk factors in advance is particularly important to predict and avoid the occurrence of PTCI.Patients and Methods: We retrospectively analyzed 297 patients with moderate to severe TBI admitted to the Department of Neurosurgery in our hospital from January 2019 to September 2020 and evaluated the effects of various factors such as age, sex, admission Glasgow Coma Scale (GCS), skull base fracture, subarachnoid hemorrhage (SAH), brain herniation, hypotensive shock, and decompressive craniectomy on the incidence of PTCI. We also performed a multivariate logistics regression analysis on the relevant factors identified and evaluated the diagnostic value of each risk factor in advance by receiver operating characteristic (ROC) analyses.Results: Among the patients, 32 (10.77%) suffered PTCI. The incidence rates of PTCI in those with GCS scores of 3– 8 and 9– 12 were 15.87% (30/189) and 1.85% (2/108), respectively, while the rates were 18.84% (13/69), 15.03% (29/193), 18.57% (13/70), and 20.59% (14/68) in those with skull base fractures, traumatic SAH, brain herniation, and hypotensive shock, respectively, and 14.38% (23/160) in those who underwent decompressive craniectomy. These differences in PTCI incidence were statistically significant. However, the differences in PTCI incidence caused by patient age and sex were not statistically significant.Conclusion: Low GCS score, skull base fractures, traumatic SAH, brain herniation, hypotensive shock, and decompressive craniectomy are risk factors for the occurrence of PTCI, while age and sex are not significantly correlated with the occurrence of PTCI.Keywords: moderate or severe traumatic brain injury, posttraumatic cerebral infarction, risk factor